Влияние геометрических характеристик выпуклых осадочных вставок на энергосиловые режимы при эксцентричной осадке заготовок различной высоты - Николенко, Р. С. (НТУ "ХПИ", 2014)
Выполнено моделирование методом конечных элементов (МКЭ) процесса эксцентричной осадки выпуклыми вставками при фиксированном значении эксцентриситета вертикальных осей заготовки и инструмента. Исследование проводили с использованием пакета для конечно-элементного анализа Deform 3D. Получены графические зависимости силы осадки заготовки от степени обжатия, геометрических характеристик деформирующего инструмента и деформируемой заготовки при различных величинах эксцентриситета.

The introduction of pre-profiling operations to achieve approximation workpiece shape configuration at stamping forging widespread in modern forging and stamping industry and is very promising in terms of the further development of technology. Performed by finite element method (FEM) of rainfall convex inserts a fixed value of the eccentricity of the axes of the workpiece and the tool. Graphic dependences obtained efforts rainfall harvesting on the degree of compression, the geometric parameters of the deformation tool and the relative height of the deformed workpiece during a eccentricity. The study of power modes for operations prior profiling will allow in the future, to clarify the methods of choice press equipment at the marginal nominal strength and safe load in the actuator with automatic modes Banded punching and profiling with combination punches per stroke of the press.
Influence of the geometric characteristics of convex upsetting die-box on the power modes at the eccentric upsetting of billets with different height
Keywords: заготовки; профилирование; выпуклые вставки; эксцентриситет; штамповка; осадка заготовки; степень обжатия; convex die-box; eccentricity; effort; workpiece; profiling